Structure-dependent performance of TiO2/C as anode material for Na-ion batteries. (February 2018) - He, Hanna; Gan, Qingmeng; Wang, Haiyan; Xu, Gui-Liang; Zhang, Xiaoyi; Huang, Dan; Fu, Fang; Tang, Yougen; Amine, Khalil; Shao, Minhua
Abstract: The performance of energy storage materials is highly dependent on their nanostructures. Herein, hierarchical rod-in-tube TiO2 with a uniform carbon coating is synthesized as the anode material for sodium-ion batteries by a facile solvothermal method. This unique structure consists of a tunable nanorod core, interstitial hollow spaces, and a functional nanotube shell assembled from two-dimensional nanosheets. By adjusting the types of solvents used and reaction time, the morphologies of TiO2 /C composites can be tuned to nanoparticles, microrods, rod-in-tube structures, or microtubes. Among these materials, rod-in-tube TiO2 with a uniform carbon coating shows the highest electronic conductivity, specific surface area (336.4 m 2 g −1 ), and porosity, and these factors lead to the best sodium storage capability. Benefiting from the unique structural features and improved electronic/ionic conductivity, the as-obtained rod-in-tube TiO2 /C in coin cell tests exhibits a high discharge capacity of 277.5 and 153.9 mAh g −1 at 50 and 5000 mA g −1, respectively, and almost 100% capacity retention over 14, 000 cycles at 5000 mA g −1 . In operando high-energy X-ray diffraction further confirms the stable crystal structure of the rod-in-tube TiO2 /C during Na + insertion/extraction. This work highlights that nanostructure design is an effective strategy to achieve advanced energy storage materials. Graphical abstract: Highlights: Hierarchical rod-in-tube structured TiO2 /C was fabricated by morphology tuning. In situ carbon coating was formed on TiO2 derived from the adsorbed solvent. Morphologies of TiO2 /C were tuned by adjusting the solvents and reaction time. SIBs using TiO2 /C HRTs exhibited superior sodium storage performance.